KEABSAHAN TENTANG KONTRAK LUMP SUM DALAM PENGADAAN BARANG DAN JASA PEMERINTAH DITINJAU DARI HUKUM KONTRAK - Septiani, Rizka Nur (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSTRACTThe government is always required to advance public welfare. To develop this obligation the government has an obligation to provide the needs of the people in various forms both in the form of goods and services in carrying out government activities. The government in carrying out its function as a builder of facilities and infrastructure or public infrastructure and as a provider in this case as a provider of needs for the people, requires the private sector as a supplier of goods and services to the government. Related to this matter there is a legal relationship between the government as a user with the private sector as a provider that is arranged in the form of a contract.The writing of this Law aims to find out the validity of the Contract Law the Lump Sum in the procurement of government goods and services is reviewed from Contract Law and to find out the legal status of the implementation of the addendum against the Lump Sum Contract that has been running.This type of research is a normative legal research with the approach of Act and conceptual. Using primary, secondary and non-legal sources of legal material. then the legal material is processed in a deductive way and then draws it into a more specific conclusion and is arranged systematically.The results of the study that the validity of the Lump Sum Contract procurement of government goods and services in terms of Contract Law is an essential (important, core, or principal) requirementÂ  in a Contract. Legal status of the implementation of the addendum to the Lump Sum Contract those who have been running in the implementation phase are considered still valid as long as the volume and Contract priceare not change. The volume can only be changed or corrected when the evaluation phase Working Group or Procurement Committee because there is an error without changing the value of the offer.Keywords: Lump Sum Contract, Procurement of goods and services, Government